Testicular echotexture and seminal quality of young Montana Tropical Compound bulls classified as sound and unsound for breeding - Rogério Oliveira Pinho; Deiler Sampaio Costa; Jeanne Broch Siqueira; Alberto Yukio Chaya; Tamires Miranda Neto; Leonardo Franco Martins; Simone Eliza Facioni Guimarães; José Domingos Guimarães (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to investigate the relationship between testicular echotexture and seminal quality, in addition to evaluate the testicular parenchyma echogenicity pattern in young Montana bulls classified as sound and unsound for breeding. Fifty-two young Montana Tropical Compound bulls from 22 to 33 months of age were used. The animals were previously evaluated by breeding soundness evaluation and thereafter divided into two groups of breeding soundness classes: 1 = 16 animals sound for breeding; 2 = 36 animals unsound for breeding by means of physical and morphological analysis of semen. All animals underwent an ultrasound examination of the testes, and the images were analyzed with the software "Image J". ANOVA was used for statistical analysis, to determine the effect of groups in relation to testicular measurements, physical and morphological semen features and ultrasound pixel analysis. There was a difference between scrotal circumference between classes, with 39.7±2.1 cm and 37.3±3.1 cm for sound and unsound animals, respectively. Regarding testicular echotexture, mean values for the pixel intensity were 95.7 and 94.0 for sound and unsound animals for breeding, respectively, with no difference between the classes. None of the studied parameters were correlated with each other, indicating that the quantification of the pixel intensity in testicular echotexture was not effective in determining the degree of sexual maturity in Montana Tropical Compound bulls.